PENGARUH KEPRIBADIAN DAN EMPLOYEE ENGANGEMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PEGAWAI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BENGKULU - Harmuji Putra; Tezar Arianto (UM. Bengkulu, 2023)
This study aims to examine the effect of Personality and Employee Engagement on Organizational Citizenship Behavior in Employees of the Office of Population and Civil Registration of the City of Bengkulu. The formulation of the problem in this study is how the influence of Personality and Employee Engagement on Organizational Citizenship Behavior in Employees of the Office of Population and Civil Registration of the City of Bengkulu. The purpose of this study is to determine the effect of Personality and Employee Engagement on Organizational Citizenship Behavior in Employees of the Office of Population and Civil Registration of the City of Bengkulu. This type of research uses a quantitative data design with primary data. The population is the Office of the Population and Civil Registration Office of the City of Bengkulu. The sampling technique used the random sampling method so that 40 respondents were selected as samples in this study. The method used in this research is explanatory research. Data analysis technique using SmartPLS. The results of the study show that the Personality variable (X1) has an effect on Organizational Citizenship Behavior with a p-value of 0.001 <0.05. The Employee Engagement variable (X2) has an effect on Organizational Citizenship Behavior with a p-value of 0.015 > 0.05. Keywords: Personality, Employee Engagement, OCB